Estuarine molecular bycatch as a landscape-wide biomonitoring tool. (September 2021) - Mariani, S.; Harper, L.R.; Collins, R.A.; Baillie, C.; Wangensteen, O.S.; McDevitt, A.D.; Heddell-Cowie, M.; Genner, M.J.
Abstract: Environmental DNA analysis is rapidly transforming biodiversity monitoring and bolstering conservation applications worldwide. This approach has been assisted by the development of metabarcoding PCR primers that are suited for detection of a wide range of taxa. However, little effort has gone into exploring the value of the non-target DNA sequences that are generated in every survey, but subsequently discarded. Here we demonstrate that fish-targeted markers widely employed in aquatic biomonitoring can also detect birds and mammals present in the surrounding habitats. We showcase this feature in three temperate estuaries over multiple seasons, where dozens of bird and mammal species offer valuable insights into spatial and temporal faunal variation. Our results indicate that existing metabarcode sequence data sets are suitable for mining and exploration of this 'molecular by-catch', and that future eDNA-based surveys can be designed to accommodate this enhanced property of this widely applicable tool. Highlights: We used an eDNA metabarcoding survey of UK coastal fishes to specifically search for non-fish taxa; Nearly 18% of sequence reads mapped to over 50 species of birds and mammals; We analysed data spatially across three estuaries, over three seasons, and found faunal patterns of conservation relevance; These non-target taxa detected, here termed "molecular bycatch", represent an important source of biodiversity information.